Konflik Kepentingan dalam Liberalisasi Perdagangan Garam Tahun 2009-2014 - Tanaem, Esti Renatalia; Arisanto, Puguh Toko (Jurnal Transformasi Global, 2021)
The trade liberalization of domestic salt sector in Indonesia indicated by tarriff reduction faced pros and contras. By using the concept of two-level games and governmental process, the authors found that there was a political upheaval of actors both from bureaucrats and interest groups adorning the political process in salt liberalization in Indonesia. Political upheaval occurred due to the tug of war between the pro and the cons. The pros, represented by Ministry of Industry, Ministry of Trade, importers and mafias supported imports of salt to meet domestic needs that cannot be fulfilled by domestic salt productions, both in quality and quantity. On the other hand, the cons represented by the Ministry of Marine Affairs and Fisheries and salt farmers both from associations and from non-associations demanded salt import reduction to support the domestic salt production program and the sustainability of the domestic salt industries.KeyWords: Liberalization of Domestic Salt, Two Level Games, Governmental Process, PoliticalÂ Upheaval, Tug of War.